Determination of tannin and saponin dosage for defaunation improvement feed fermentability - I.M. D. Wahyuni; A. Muktiani; M. Christianto (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2014)
The research was conducted to evaluate the effect of addition of tannin, saponin or combination of tannin and saponin to the concentrate of the ration on the microbial population and fermentability of feed in vitro and to assess the best dosage of uses. The research was arranged according to completely randomized design with four treatments and 3 replications. The treatments were ration without tannin and saponin (T0), ration with 1.2% saponin (T1), ration with 0.5% tannin and 0.9% saponin (T2), ration with 1% tannin and 0.6% saponin, (T3), ration with 1.5% tannin and saponin 0.3% (T4) and ration with 2% tannin and 0% saponin. the results of the experiment showed that the addition of the tannin, saponin or their combination altered microbial population in the rumen. Protozoas population decreased significantly whereas bacterial population was increased. NH3 production increased while ratio of acetaic to propionic acid tended to decrease. Total gas production increased 62.59-69.35 ml/200 mg of dry matter. The addition of 1% tannin and 0.6 % saponin shows the best effect to control protozoa population and feed fermentability in the rumen.